Vascular Leiomyoma and Geniculate Ganglion - Magliulo, Giuseppe; Iannella, Giannicola; Valente, Michele; Greco, Antonio; Appiani, Mario Ciniglio (Journal of Neurological Surgery Reports, 2013)
Objectives Discussion of a rare case of angioleiomyoma involving the geniculate ganglion and the intratemporal facial nerve segment and its surgical treatment.Design Case report.Setting Presence of an expansive lesion englobing the geniculate ganglion without any lesion to the cerebellopontine angle.Participants A 45-year-old man with a grade III facial paralysis according to the House-Brackmann scale of evaluation.Main Outcomes Measure Surgical pathology, radiologic appearance, histological features, and postoperative facial function.Results Removal of the entire lesion was achieved, preserving the anatomic integrity of the nerve; no nerve graft was necessary. Postoperative histology and immunohistochemical studies revealed features indicative of solid vascular leiomyoma.Conclusion Angioleiomyoma should be considered in the differential diagnosis of geniculate ganglion lesions. Optimal postoperative facial function is possible only by preserving the anatomical and functional integrity of the facial nerve.
Keywords: vascular leiomyoma; geniculate ganglion; surgery; facial preservation